Living Hadith: Etika Makan dan Minum Mahasiswa - Riza Wardefi; Muhammad Hidayat; Rahmi Wiza (Jurnal Kawakib, 2025)
This article is motivated by the differences in the eating and drinking practices of students with the hadith of the Prophet SAW. The problem in this study is to analyze the eating and drinking ethics of students at Padang State University (UNP). The object of this study is UNP students, on the grounds that the majority of students here are Muslim and have a strong Minangkabau culture with Islamic values. The concept of living hadith is a study of hadith that lives in society based on the hadith of the Prophet SAW. The research method used is a descriptive qualitative method based on a case study approach. The analysis of this study uses a SWOT analysis. The results of the study indicate that the eating and drinking practices of UNP students on campus are currently generally not in accordance with the ethical values ​​of eating and drinking in Islamic teachings.